Analisis Kemampuan Representasi Matematis Siswa dalam Menyelesaikan Soal Matematika Materi SPLDV - Feri Virnando; Nurhanurawati; Agung Putra Wijaya (Mandalika Mathematics and Educations Journal, 2026)
This study aims to analyze how junior high school students express their ideas when solving problems related to the System of Linear Equations in Two Variables (SPLDV). Mathematical Representation Ability is essentially a "bridge" for students to transform difficult and abstract mathematical concepts into more real and simple forms, whether through images, symbolic formulas, or written explanations. SLETV was chosen due to its characteristics that involve complex word problems, requiring students to be proficient in converting long narratives into correct mathematical models. Through a literature review method analyzing various previous research findings, it was found that students' representation abilities are heavily influenced by their basic mathematical proficiency levels. High-achieving students are generally proficient in using symbols and graphs, yet they still face challenges in providing narrative explanations for their reasoning. Meanwhile, low-achieving students and slow learners show significant obstacles in initiating problem-solving, thus requiring specific assistance or scaffolding.